Transformasi Pendidikan Perempuan Dari Tradisional Ke Modern di Seberang Kota Jambi - Maisah Maisah (Kafa`ah: Journal of Gender Studies, 2019)
Women's past Education in Seberang Kota Jambi had several limitation. Women only studied religious education since  general education is considered for infidels. Transactional education of women to the modern  were caused by several factors and people may lose their trust in the scholars. Development of infrastructure  can help women to increase their ability to taste higher education. Then women's education in modern times has changed 180 degrees when and the technology always entails the women career live as well as modern information era since these two issues are recognized as the factors in equalized their job opportunity.